Mastery of Essential Mathematics Concepts : How it Enhances Students’ Critical and Creative Thinking Skills - Ayu Aristika (Lembaga Pengembangan Kinerja Dosen, 2025)
This study is a descriptive and correlational study to investigate students’ mastery of essential mathematics concept and find the connection to their critical and creative thinking. The subjects of the study consisted of 234 junior high school students from various schools in high, average, and low qualities. The results of the study indicated that 1) Students’ mastery of essential mathematics concept are at average level; 2) The difficulties that encountered by the students come from internal factor (themselves), and external factors (teachers, the characteristics of mathematics, schoolmates and the facilities; 3) There is a significant relationship between students’ mastery of essential mathematics concept and their critical thinking; 4) The correlation between the ability to be skilled in essential math concept and their creative thinking is at high level.